Strengthening the Adoption of Learner-Centred Pedagogies in Teacher Education in Uganda through Video-Based Self Reflection & College-Based Mentorship System (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
The intermittent pedagogical support received by teacher-trainers from the central level makes it difficult to implement new practices in teacher training institutions in Uganda. This mixed-methods study investigated teacher-trainers’ perceptions of a pilot pedagogical support system implemented by college-based mentors. Qualitative and quantitative data were elicited using an online questionnaire completed by teacher- trainers (n=100) and video-records of interviews with selected college-based mentors (n=6) who reflected on their own experiences to propose ways of improving the system. The findings revealed that irrespective of years of experience, teacher-trainers appreciate the contribution of college-based mentors towards the adoption of learner-centred pedagogy. It also revealed that the opportunity for self-reflection and collegial critique afforded by video enhanced the practices of the mentees and greatly enriched the mentorship process. Nonetheless, the teacher-trainers expressed the need to broaden mentorship activities to include subject-specific pedagogical support.
Keywords: Learner-centred pedagogy; College–Based Mentorship; Reflective Practice Mixed-methods study; teacher-trainers; video-records; self-reflection; collegial critique